Interleukin-1 Receptor Antagonist Gene VNTR Polymorphism is Associated with Coronary Artery Disease - (:unkn) unknown (ARQUIVOS BRASILEIROS CARDIOLOGIA, 2008)
Background: Coronary Artery Disease (CAD) is the atherosclerosis of coronary arteries that carry blood to the heart muscle. Atherosclerosis is an inflammatory disease. Cytokine gene variations such as those associated with the IL1 family are involved in the pathogenesis of atherosclerosis. Objective: The purpose of this study was to determine the relationship between IL1 family polymorphisms (IL1RN VNTR, IL1B positions -511 and +3953) and CAD in Turkish population. Methods: 427 individuals were submitted to coronary angiography and were grouped as 170 control subjects and 257 CAD patients. The CAD subjects were divided into two subgroups: 91 Single Vessel Disease (SVD) and 166 Multiple Vessel Disease (MVD) subjects. The genotypes of IL1RN and of IL1B (-511, +3953) were determined by polymerase chain reaction (PCR) followed by restriction digestion analysis. Results: No significant difference was found in IL1RN and IL1B (-511 and +3953) genotype distributions between CAD and control subjects or MVD and control subjects. However, significant association was seen in IL1RN 2/2 genotype between SVD and control subjects (P = 0.016, x2: 10.289, OR: 2.94, 95% CI: 1.183-7.229). Similarly, no statistically significant difference was found in IL1RN and IL1B (-511 and +3953) allele frequencies between CAD and control subjects, MVD and control subjects or SVD and control subjects. Conclusion: No association was found in either allele frequency or genotype distribution of IL1RN and IL1B polymorphisms between CAD and the control groups. However; IL1RN 2/2 genotype may be a risk factor for SVD in the Turkish population. (Arq Bras Cardiol 2008; 91(5) : 268-273)
Keywords: Interleukin 1; mini-satellite repeats; coronary arteriosclerosis; population; Turkey / epidemiology; MYOCARDIAL-INFARCTION; RHEUMATOID-ARTHRITIS; TANDEM REPEAT; PLASMA-LEVELS; IL-1; INTRON-2; ATHEROSCLEROSIS; SECRETION; PROTEIN; RISK